Curriculum Development Management Model for International-Standard Madrasas: Evidence from Indonesia - Asdlori; Hanif, Muh.; Efendi, Arief; Ndow, Muhammed; Purnama, Yulian (Indonesian Academy of Social and Religious Research (IASRR), 2026)
This study formulates an empirically grounded curriculum development management model for international-standard madrasas in Indonesia, responding to globalization and uneven curriculum innovation. Prior studies often theorize internationalization or describe technical integration; this article clarifies how governance routines coordinate mapping, capacity, and evaluation. A qualitative grounded theory design examined two cases MBI Amanatul Ummah (Mojokerto) and the Mu’allimaat International Class Program (Yogyakarta) using purposive informants (principals, vice principals, and international-class teachers), semi-structured interviews, observations, and document analysis; data were analyzed with the Miles–Huberman–Saldaña interactive model. The model comprises three interlocking domains: (1) integrated curriculum design that maps national and Ministry of Religious Affairs competencies to Cambridge objectives and delivers them through a blended/LMS-supported “glocal” approach; (2) human-resource and language capacity building via selective recruitment, continuous English–Arabic upskilling, and TOEFL/TOAFL readiness; and (3) results-based quality assurance through exam analytics, MGMP-style professional review, transparent parent reporting, and sister-school collaboration. Together, these routines convert multiple standards into a coherent instructional logic and sustain continuous improvement through a measurable feedback loop. International-standard madrasas can reach global benchmarks without losing Islamic-local identity by mapping standards, building people, and institutionalizing data-driven review. This transferable framework guides policymakers seeking scalable madrasa reform across Indonesia.